Treatment of oil–water emulsions by adsorption onto activated carbon, bentonite and deposited carbon - Khaled Okiel; Mona El-Sayed; Mohamed Y. El-Kady (Egyptian Journal of Petroleum)
Emulsified oil in waste water constitutes is a severe problem in the different treatment stages before disposed off in a manner that does not violate environmental criteria. One commonly used technique for remediation of petroleum contaminated water is adsorption. The main objective of this study is to examine the removal of oil from oil–water emulsions by adsorption on bentonite, powdered activated carbon (PAC) and deposited carbon (DC). The results gave evidence of the ability of the adsorbents to adsorb oil and that the adsorptive property of the three adsorbents (bentonite, PAC, and DC) has been influenced by different factors. The effects of contact time, the weight of adsorbents and the concentration of adsorbate on the oil adsorption have been studied. Oil removal percentages increase with increasing contact time and the weight of adsorbents, and decrease with increasing the concentration of adsorbate. Equilibrium studies show that the Freunlich isotherm was the best fit isotherm for oil removal by bentonite, PAC, and DC. The data show higher adsorptive capacities by DC and bentonite compared to the PAC.